Steel-rolling technology theory and practice - Ginzburg, Vladimir B. (Manufacturing engineering and materials processing, 1989)
"This state-of-the-art volume examines steel-rolling technology in a systematic and comprehensive manner--providing an excellent synthesis of current information from three different branches of science--physics, metallurgy, and engineering. "